Study of Zn(O, S) films grown by aerosol assisted chemical vapour deposition and their application as buffer layers in Cu(In, Ga)(S, Se)2 solar cells. (May 2015) - Kriisa, Merike; Sáez-Araoz, Rodrigo; Fischer, Christian-Herbert; Köhler, Tristan; Kärber, Erki; Fu, Yanpeng; Hergert, Frank; Lux-Steiner, Martha Christina; Krunks, Malle
Highlights: Zn(O, S) layers were grown by aerosol assisted chemical vapour deposition. Zn(O, S) is a potential substitute for CdS and In2 S3 as buffers in solar cell. Safe and cheap Zn(O, S) allows to prepare solar cells with simpler structure. Two recipes were determined for depositing compact Zn(O, S) layers. Zn(O, S) buffered cell output characteristics are comparable to CdS and In2 S3 cells. Abstract: Manufacturing chalcopyrite thin film solar cells from cost-efficient and environmentally friendly materials is of high priority. Therefore, the materials used in buffer layer production nowadays (such as indium and cadmium) need to be substituted. Zn(O, S) is considered to be a potential buffer layer material when deposited with a fast and inexpensive method. Zn(O, S) layers have been prepared by aerosol assisted chemical vapour deposition (AACVD) technique. AACVD technique is a simple non-vacuum process where the thin film deposition temperatures do not exceed 250 °C. 10 mM spray solution was made by dissolving zinc(II)acetylacetonate monohydrate in ethanol. The films were grown on Mo substrate at 225 °C (film growth temperature). The effect of deposition parameters (spray solution concentration, N2 flow rate, H2 S flow rate) on Zn(O, S) thin film properties were studied with SEM and XRD. Thereupon optimising the deposition parameters, homogeneous and compact Zn(O, S) thin films were obtained and the films were employed in the chalcopyrite thin film solar cell structure by growing films on Cu(In, Ga)(S, Se)2 substrates industrially produced by BOSCH Solar CISTech GmbH. The resulting cells were studied using current–voltage and quantum efficiency analysis and compared with solar cell references that include In2 S3 and CdS as buffer layer deposited by ion layer gas reaction and chemical bath deposition, respectively. The best output of the solar cell containing Zn(O, S) as buffer layer and without intrinsic ZnO under standard test conditions (AM 1.5G, 100 mW/cm 2, 25 °C) is: Voc = 573 mV, Jsc = 39.2 mA/cm 2, FF = 68.4% and efficiency of 15.4% being slightly better than the In2 S3 or CdS containing solar cell references.